2020
DOI: 10.1111/wej.12652
|View full text |Cite
|
Sign up to set email alerts
|

Plastics waste identification in river ecosystems by multispectral proximal sensing: a preliminary methodology study

Abstract: A considerable amount of the plastics produced around the world is now dispersed throughout the environment, and in particular in aquatic ecosystems. This can have damaging consequences for plants, animals and human beings. This study investigates some approaches for detection and monitoring of plastics waste in river habitats through multispectral image classification. The data are acquired using a proximity sensor in the electromagnetic spectrum range that includes the ultraviolet, visible and near infrared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Recently, remote sensing (RS) that collects multi-to hyperspectral imagery has started to show far-reaching potential for the detection and monitoring of riverine and marine plastic pollution [13,14]. For example, Topouzelis, et al [15] and Themistocleous, et al [16] successfully identified large artificial plastic targets in coastal zones using Sentinel-2 imagery.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, remote sensing (RS) that collects multi-to hyperspectral imagery has started to show far-reaching potential for the detection and monitoring of riverine and marine plastic pollution [13,14]. For example, Topouzelis, et al [15] and Themistocleous, et al [16] successfully identified large artificial plastic targets in coastal zones using Sentinel-2 imagery.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it is possible to capture up to 25 bands in different spectral ranges in a single shot. These new features allow spectral imaging to expand to new areas of use that were unthinkable a few years ago, such as disease [ 5 ] or water stress detection [ 6 ] in crops from on-board drones or autonomous robots, food inspection [ 7 ], material classification [ 8 ], cancer diagnosis [ 9 ], or plant phenotyping [ 10 ], among others. A difference between hyperspectral and multispectral sensing technology is the extent of the reflectance spectrum captured.…”
Section: Contextmentioning
confidence: 99%
“…Recently, remote sensing (RS) collecting multi-to hyperspectral imagery has started to show far-reaching potential for detection and monitoring of riverine and marine plastic pollution [13,14]. For example, Topouzelis et al [15] and Themistocleous et al [16] successfully identified large artificial plastic targets in coastal zones using Sentinel-2 imagery.…”
Section: Introductionmentioning
confidence: 99%